2017
DOI: 10.3906/zoo-1702-17
|View full text |Cite
|
Sign up to set email alerts
|

Unusual winter zooplankton bloom in the open southern Adriatic Sea

Abstract: The paper reports an unusual response of the microzooplankton community to oceanographic conditions observed during the winter of 2015 in the open southern Adriatic. Record-breaking nauplii abundance of 13,734 ind. m -3 was sampled for the open southern Adriatic by 50-µm net sampling. This could be explained by (i) warmer-than-usual surface and intermediate ocean temperatures, (ii) higher precipitation that freshened and widened the surface layer, pushing saline Levantine Intermediate Water below a 400-m depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The community was characterized by the presence of surface and subsurface oceanic tintinnid species in April in the deep layers, which indicated that they can survive for more than a month in the deep, since vertical mixing at the open sea usually ceases by the end of February and beginning of March [28,33]. The greater part of the mesopelagic population was made up of subsurface oceanic species Undella claparedei and Codonella amphorella, especially in the layer from 100 to 300 m. This is in accordance with the vertical distribution of tintinnids in the open southern Adriatic during the winter convection events of 2008 [43] and 2015 [34]. Our data are comparable with those that were recorded in April 1986 in the open SA when some similar hydrographic/hydrological and biological characteristics were recorded: strong LIW inflow, downward transport, and phytoplankton bloom [12,50].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The community was characterized by the presence of surface and subsurface oceanic tintinnid species in April in the deep layers, which indicated that they can survive for more than a month in the deep, since vertical mixing at the open sea usually ceases by the end of February and beginning of March [28,33]. The greater part of the mesopelagic population was made up of subsurface oceanic species Undella claparedei and Codonella amphorella, especially in the layer from 100 to 300 m. This is in accordance with the vertical distribution of tintinnids in the open southern Adriatic during the winter convection events of 2008 [43] and 2015 [34]. Our data are comparable with those that were recorded in April 1986 in the open SA when some similar hydrographic/hydrological and biological characteristics were recorded: strong LIW inflow, downward transport, and phytoplankton bloom [12,50].…”
Section: Discussionsupporting
confidence: 73%
“…The high diversity of species and low abundances at the central stations of the SA, as well as high abundance at the perimeter stations towards the shoreline observed in December 2015, are a typical feature of the Adriatic Sea for winter and early spring that is already documented in many studies while using the same sampling methods [11][12][13][14]31,34]. The observed abundance distribution was positively correlated with the temperature and Chl-a.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…( Acartiura ) clausi , T. stylifera ) were recorded in the deepest layers in 2015, when Lučić et al. () noted neritic tintinnids below 500 m depth.…”
Section: Discussionmentioning
confidence: 99%
“…Chl a concentrations were several times higher in 2016, but owing to strong wind episodes and deep‐water convection in the winter of 2015, nutrients were advected from the coastal area to the open sea and vertically displaced. These unusual 2015 wintertime conditions were reflected in highly increased values of microzooplankton (nauplii and copepodites) down to the 300 m depth (same cruise – Feb–Mar 2015; Lučić et al., ).…”
Section: Discussionmentioning
confidence: 99%